Managing a challenging diabetic foot ulcer in a patient with end-stage renal disease. Issue 1 (2019) - Sulaiman, Nor Sunihaliza Binti Salimuan; Mahroob, Mas Anida Binti; Manap, Mariam Binti Abdul
No abstract available